A comparison study of the performance of Ag2CO3 photocatalysts synthesized respectively in a surfactant-free microemulsion, water, and a water/propan-2-ol mixture - Ning Pan; Shuhui Liu; Ying Han; Dejie Li; Jinling Chai (Journal of Materiomics, 2022)
A comparison study was conducted on the performance of the Ag2CO3 visible light catalysts synthesized in a surfactant-free microemulsion (SFME), water and water/propan-2-ol mixture, respectively. The XPS spectra show that all the synthesized Ag2CO3 products have good purity. The SEM, XRD, BET and DRS characterizations indicate that the Ag2CO3 product synthesized in the SFME template has higher crystallinity, more regular morphology, more uniform size, larger specific surface area, and stronger visible light absorption performance, thus having better catalytic photodegradation activity for rhodamine B (RhB), methylene blue (MB) and methyl orange (MO). When the degradation time reaches 45 min, the degradation rate of RhB is as high as 99.11 %. Na2CO3 has a good stabilizing effect when its concentration is 0.001 mol L−1. This research is of great significance to expand the application of SFMEs in the synthesis of high-efficiency catalytic materials.